Halal certification in slaughtering industry: issues, problems and actions = Persijilan Halal dalam industri sembelihan: isu, masalah dan tindakan - Ghazali, Mohd Al'Ikhsan; Awang, Md Daud; Md Sawari, Siti Salwa; Yunos, Nasruddin; Saroji, Azis Jakfar (Laboratory of Halal Policy and Management Halal Products Research Institute Universiti Putra Malaysia, 2018)
Halal certification in Malaysia has been growing rapidly to several industries including the slaughtering industry. A continuous halal control needs to be properly executed to ensure that the process meets the halalan toyyiba. The industry of poultry processing has now become a globally-cultivated field. The application of the latest technology is inevitable but must be comply with the Shariah rules and regulations that have been outlined by the authorities. The principle of fixed and flexible (thabat dan murunah) in Islam has never contradict with the development of science and technology. The halal processing chain, especially at slaughtering premises, is very vulnerable to inaccuracy. The failure of the industry to meet the halalan toyyiba aspects can adversely affect the quality of the slaughtered products and even more serious, a non-halal slaughter. Ulama and Islamic Scholar are always willing to deal with severe parties to discussing regarding to the latest technology as not contradict with the Shari'a. Hence, The Islamic Religious Department throughout Malaysia government has implemented a Halal Critical Control Point which is a risky part for the incidence of inefficiency contamination in the slaughter process. Although, the tight monitoring has been instigated to ensure the halal quality but non-compliance issues are still addressed. JAKIM has itemized categories of offenses and actions to any party who do not comply the rules through the issue of incompatibility in slaughtering industry. The higher authorities need to monitor continuously and immediate action should be taken for improving the quality of halal regulation management internally and also assisting in the enhancement of halal management. ********************************************************* Persijilan halal di Malaysia telah berkembang pesat menerajui banyak industri termasuklah industri sembelihan yang merupakan bidang yang amat krusial. Ini kerana semua produk pedaging perlu memenuhi piawaian dan standard sembelihan yang berlandaskan syara untuk memastikan produk yang terhasil adalah halal. Bidang pemprosesan ayam kini telah menjadi bidang yang diceburi secara global. Penggunaan teknologi terkini tidak dapat dielak namun demikian mesti disesuaikan agar patuh syariat dan ketetapan yang telah digariskan oleh pihak berwajib. Ciri-ciri tetap dan fleksibel (thabat dan murunah) dalam Islam tidak pernah menghalang perkembangan sains dan teknologi. Para Ulama dan Ilmuan Islam pula sentiasa bersedia berbincang dengan pelbagai pihak untuk mendapat pencerahan berhubung dengan penggunaan teknologi terkini agar tidak bercanggah dengan syariat. Pihak Jabatan Agama Islam seluruh Malaysia telah mengemukakan Titik Kawalan Kritikal Halal yang merupakan bahagian yang berisiko untuk berlakunya ketidakakuran/pencemaran dalam proses sembelihan. Walaupun pemantauan ketat telah di laksanakan untuk memastikan kualiti halal terjamin, namun isu-isu ketidakakuran tetap berlaku. Pihak JAKIM telah menyenaraikan kategori kesalahan berserta tindakan yang boleh dikenakan kepada mana-mana pihak yang tidak akur atau patuh kepada peraturan yang telah ditetapkan. Berikutan isu ketidakakuran di premis-premis sembelihan masih berlaku di negara ini, maka pemantauan yang berterusan daripada pihak berkuasa perlu terus di laksanakan dan tindakan segera perlu diambil.